HIGH SENSITIVE PCR METHOD FOR DETECTION OF PATHOGENIC Leptospira spp. IN PARAFFIN-EMBEDDED TISSUES - Noda, Angel Alberto; Rodríguez, Islay; Rodríguez, Yaindrys; Govín, Anamays; Fernández, Carmen; Obregón, Ana Margarita (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
This study describes the development and application of a new PCR assay for the specific detection of pathogenic leptospires and its comparison with a previously reported PCR protocol. New primers were designed for PCR optimization and evaluation in artificially-infected paraffin-embedded tissues. PCR was then applied to post-mortem, paraffin-embedded samples, followed by amplicon sequencing. The PCR was more efficient than the reported protocol, allowing the amplification of expected DNA fragment from the artificially infected samples and from 44% of the post-mortem samples. The sequences of PCR amplicons from different patients showed >;99% homology with pathogenic leptospires DNA sequences. The applicability of a highly sensitive and specific tool to screen histological specimens for the detection of pathogenic Leptospira spp. would facilitate a better assessment of the prevalence and epidemiology of leptospirosis, which constitutes a health problem in many countries.